Tropospheric bromine monoxide vertical profiles retrieved across the Alaskan Arctic in springtime - Brockway, Nathaniel; Peterson, Peter K.; Bigge, Katja; Hajny, Kristian D.; Shepson, Paul B.; Pratt, Kerri A.; Fuentes, Jose D.; Starn, Tim; Kaeser, Robert; Stirm, Brian H.; Simpson, William R. (Atmospheric chemistry and physics, 2024)
Reactive halogen chemistry in the springtime Arctic causes ozone depletion events and alters the rate of pollution processing. There are still many uncertainties regarding this chemistry, including the multiphase recycling of halogens and how sea ice impacts the source strength of reactive bromine. Adding to these uncertainties are the impacts of a rapidly warming Arctic. - - We present observations from the CHACHA (CHemistry in the Arctic: Clouds, Halogens, and Aerosols) field campaign based out of Utqiaġvik, Alaska, from mid-February to mid-April of 2022 to provide information on the vertical distribution of bromine monoxide (BrO), which is a tracer for reactive bromine chemistry. Data were gathered using the Heidelberg Airborne Imaging DOAS (differential optical absorption spectroscopy) Instrument (HAIDI) on the Purdue University Airborne Laboratory for Atmospheric Research (ALAR) and employing a unique sampling technique of vertically profiling the lower atmosphere with the aircraft via “porpoising” maneuvers. Observations from HAIDI were coupled to radiative transfer model calculations to retrieve mixing ratio profiles throughout the lower atmosphere (below 1000 m), with unprecedented vertical resolution (50 m) and total information gathered (average of 17.5 degrees of freedom) for this region. - - A cluster analysis was used to categorize 245 retrieved BrO mixing ratio vertical profiles into four common profile shapes. We often found the highest BrO mixing ratios at the Earth's surface with a mean of nearly 30 pmol mol−1 in the lowest 50 m, indicating an important role for multiphase chemistry on the snowpack in reactive bromine production. Most lofted-BrO profiles corresponded with an aerosol profile that peaked at the same altitude (225 m above the ground), suggesting that BrO was maintained due to heterogeneous reactions on particle surfaces aloft during these profiles. A majority (11 of 15) of the identified lofted-BrO profiles occurred on a single day, 19 March 2022, over an area covering more than 24 000 km2, indicating that this was a large-scale lofted-BrO event. - - The clustered BrO mixing ratio profiles should be particularly useful for some MAX-DOAS (multi-axis DOAS) studies, where a priori BrO profiles and their uncertainties, used in optimal estimation inversion algorithms, are not often based on previous observations. Future MAX-DOAS studies (and past reanalyses) could rely on the profiles provided in this work to improve BrO retrievals.
Gesehen am 20.08.2024